Law Enforcement, Human Rights Protection, And Challenges Faced by SOEs and SOE Subsidiaries (Post Constitutional Court Decision Number 01/PHPU-PRES/XVII/2019) - Binsar Jon Vic S (Sociological Jurisprudence Journal, 2023)
Business transformation, law enforcement, and safeguarding human rights are pivotal global concerns applicable to all nations and jurisdictions. These issues present notable challenges, particularly for State-Owned Enterprises (SOEs) and their subsidiaries. This has been underscored in the discourse surrounding Constitutional Court Decision Number 01/PHPU-PRES/XVII/2019, which implicitly recognizes SOE Subsidiaries as problematic elements within corporate operations. A central inquiry arising from this context is how the regulations governing SOEs and their subsidiaries' activities have evolved subsequent to the aforementioned Constitutional Court Decision. The research employs a normative juridical legal approach, drawing on primary sources such as regulations and statutes pertinent to the case, along with secondary data. The primary objective of this study is to offer legal insights to law enforcement bodies and institutions directly involved with State-Owned Enterprises and their subsidiaries. These entities are anticipated not only to enhance profitability but also to function as catalysts for societal well-being. The findings of this research underscore the vital role played by SOEs and their subsidiaries in aiding corporate restructuring, upholding legal standards, and advocating for human rights, both internally and externally.